FRI0250 Involvement of Salivary Glands in Primary SjÖGren's Syndrome. Elastographic Assessment and Correlations with Ultrasonographic Findings. (10th June 2014) - Iagnocco, A.; Iorgoveanu, V.; Priori, R.; Gattamelata, A.; Finucci, A.; Carrara, G.; Scirè, C.A.; Valesini, G.
Abstract : Background: Primary Sjögren's Syndrome (SS) is an autoimmune disease characterized by early inflammatory abnormalities of salivary and lacrimal glands and subsequent progressive destruction and local fibrosis. Imaging evaluation of salivary gland involvement in SS is still a matter of debate, with different tools that may be used. Ultrasound (US) has high sensitivity and specificity in the evaluation of parotid and submandibular glands involvement in SS (1). Elastography (UE) is a new technique that has been recently used for assessing skin and tendon elasticity in rheumatic diseases (2). However, as far as we know no study is present in the literature about elastographic assessment of salivary gland in SS. Objectives: To evaluate the involvement of salivary glands in SS by UE and to correlate elastographic findings with US-detected abnormalities. Methods: Salivary glands of consecutive SS patients and healthy controls were examined by UE and US by an experienced ultrasonographer who was blinded to the clinical findings. The study was performed with a MyLab70 XVG (Esaote, Italy) machine equipped with a multifrequency linear probe (4-13 MHz) and elastographic software. Parotid and submandibular glands were studied bilaterally by US firstly and graded according to a 0-4 score (1). Then, UE was carried out by sequential movements of compression and decompression of the probe over the region of interest and the resulting color assessment varied from red (indicative of soft and highly elastic tissue), to green (which represented intermediate elastic tissue), and to blue (which denoted hard and barely elastic tissue). Elastographic findings were scored according to the local color prevalence. The association between US and UE score was evaluated by the Spearman's correlation coefficient, and discrimination between cases and control by the area under the ROC curve (AUC). Results: 328 salivary glands of 82 patients with SS [80 (97.6%) female; mean (sd) age 53.5 (12.3); median (IQR) disease duration in months 21 (1-192) and 116 glands of 29 aged matched healthy individuals [21 (72.4%) female; mean (sd) age 48.7 (13.5)] were studied. A significant correlation between the total UE and the US score was found (0.68; p<0.0001) and was mainly due to the blue component (green -0.62, p<0.0001; red 0.05, p=0.59; blue 0.65, p<0.0001). In addition, both US (AUC =0.961) and UE (AUC =0.817) scores were able to discriminate between SS patient and healthy controls. Conclusions: UE is a valuable imaging tool in the assessment of salivary gland abnormalities in SS patients and may represent a good option as a first-line imaging modality in the diagnostics of the disease. References: Salaffi F, Carotti M, Iagnocco A et al Ultrasonography of salivary glands in primary Sjögren's syndrome: a comparison with contrast sialography and scintigraphy. Rheumatology 2008;47:1244-9. Iagnocco A, Kaloudi O, Perella C et al Ultrasound elastography assessment of skin involvement in systemic sclerosis: lights and shadows. J Rheumatol 2010;37:1688-91 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3419